The comparison of the effect of executive function training and social emotional training on the performance of continuous attention in in students with mathematical learning disability in elementary schools - Parisa Khosrotash; Khadijeh Abolmaali Alhosseini; kianoosh Hashemian (Ravānshināsī-i Afrād-i Istis̠nāyī, 2017)
The purpose of this study was to compare the effect of executive function and social-emotional training on performance of continuous attention (the correct answer to image and numbers, reaction time about images and reaction time about numbers) among the girl students with learning disability in 3-5 grades at district 5 in Tehran. The method of this research was quasi-experimental and pre- test and post- test with control group design. For identifying students with mathematical learning disability was used Diagnostic and Statistical Manual of Mental Disorders- 5, Raven test, and Iran Key math diagnostic test. Identified students were randomly assigned to two experimental groups and one control group (n= 7, in each group). They did performance of continuous attention test in pre-test and post-test. The first and second experimental groups received executive function and social-emotional training respectively, and control group did not receive any treatment. The data were analyzed with MANCOVA. Results showed that social-emotional training leads to improve performance of continuous attention (in the correct answer to images and numbers, and reaction time about numbers). Effectiveness of executive function training on performance of continuous attention is not significant, and there is not significant difference between the effects of executive function training and social - emotional training on the performance of continuous attention. In general, it can be concluded that sociol-emotional learning is a good way to increase performance of continuous attention in students with mathematical learning disorders.